Analisis Keselarasan Dokumen Perencanaan, Penganggaran, Dan Akuntabilitas Kinerja Satuan Kerja Perangkat Daerah (Studi Kasus Pada Dinas Kebudayaan dan Pariwisata Aceh) - Putri Ayudia; Syukriy Abdullah (Jurnal Riset AKuntansi dan Bisnis, 2023)
This study was conducted to analyze the alignment/consistency of planning, budgeting, and performance accountability documents in the SKPD, namely in the Strategic Plan, Renja, DPA-SKPA, LKPJ, and LAKIP (Realization) documents for the 2018-2019 This study aims to identify the causes of misalignment/inconsistency in planning, budgeting, and performance accountability by comparing the level of consistency of programs/activities through the budget on each document to be analyzed. This research uses a descriptive qualitative method with a case study approach at the Aceh Culture and Tourism Office. The type of data was collected through observation techniques, documentation, and direct interviews with officials/employees of the Aceh Disbudpar. Participants in this study were officials or employees involved in the planning and budgeting process. The document analysis results showed that the performance of the SKPA DPA budget with the realization of the Aceh Disbudpar budget in 2018 was 52 percent (deficient) and in 2019 it was 22 percent (deficient). The cause of the inconsistency of planning documents, budgeting, and performance accountability is the inconsistency between the goals and targets of the organization and the work units below it, monitoring performance achievements is still limited to financial aspects, performance achievements are not used as the primary basis.